2018
DOI: 10.1097/pai.0000000000000509
|View full text |Cite
|
Sign up to set email alerts
|

Differential Expression of Cytochrome C Oxidase Subunit I Along the Colorectal Adenoma: Carcinoma Progression

Abstract: Loss in apoptosis competence often results in augmented genomic instability contributing to carcinogenesis. Cytochrome c oxidase subunit I (CcOI) can help assess apoptosis resistance in paraffin-embedded biopsies. In total, 50 colorectal cases including 10 control cases of colectomy for non-neoplastic condition, 15 cases of adenomatous colorectal polyps, and 25 cases of colorectal carcinoma were investigated in this retrospective study for immunohistochemical expression of CcOI. The staining pattern of CcOI wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…22 CRC arises in a field of crypts with abnormal expression of COX1. 23 This evidence suggests that COA1 may play an important role in CRC. The present study suggested that COA1 expression in CRC was significantly associated with pathological differentiation, tumor size, and tumor depth.…”
Section: Dovepressmentioning
confidence: 96%
“…22 CRC arises in a field of crypts with abnormal expression of COX1. 23 This evidence suggests that COA1 may play an important role in CRC. The present study suggested that COA1 expression in CRC was significantly associated with pathological differentiation, tumor size, and tumor depth.…”
Section: Dovepressmentioning
confidence: 96%
“…Six of these ten nuclear-encoded subunits can be replaced by isoforms, leading to heterogeneity in the composition and activity of this large complex [ 19 ]. Recently, defects or irregular expression of subunits in COX have been associated with tumorigenesis or progression in several types of cancers, including hepatocellular carcinoma (HCC), glioma, breast cancer, and CRCs [ 20 , 21 , 22 , 23 ]. However, the roles of the subunits are unclear; some are oncogenic, whereas others are suppressive in these cancers.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that in the macrocomplex, six of these nuclear-encoded subunits could be replaced by isoforms to retain full enzymatic activity, suggesting marked heterogeneity in the composition of this large complex and activity (for a review, see reference [16]). Recently, defects or aberrant expressions of subunits in COX have been associated with clinical prognosis in several types of cancers, including colorectal cancer, glioma, breast and hepatoma [17][18][19][20][21]. However, the actual growth regulatory roles of these subunits have not been clearly investigated.…”
Section: Introductionmentioning
confidence: 99%